Telesna samopodoba kot pomemben motivacijski dejavnik za gibalno/športno aktivnost otrok in mladostnikov - Dolenc, Petra (Revija za elementarno izobraževanje, 2010)
Physical self-conception as an important motivational factor for physical activity among children and adolescents. Self-conception is a multidimensional construct that refers to an individual’s perception of »self«. This percepion not only affects the psychological well-being of children and adolescents but also their motivation and behaviour. The formation of their self-conception represents an important developmental task in childhood and adolescence. Research findings suggest that one’s self conception becomes more varied and complex with age. The multidimensionality of self-conception em- phasizes that people have different perceptions of themselves in specific domains of life. Physical self-conception is seen as the primal and most elementary dimension of global self-conception, since it starts to develop in the earliest period of an individual’s life and is crucial for the formation of other facets of self-conception. Research carried out on the physical self-conception of children and adolescents are useful and necessary, not only in relation to their physical/sports activity, but also in terms of promoting the development of their physical self, which in turn will have a positive effect on the global self-conception and self-esteem of children as well. The aim of this research was to determine the extent of children’s physical self-conception and to introduce the available instruments for assessing the physical self-conception of children and adolescents. Recent research findings in this field are also included. The article emphasises the motivational role of children’s physical self-conception for the purpose of engaging in physical activities.